2014
DOI: 10.1007/s12010-014-1395-z
|View full text |Cite
|
Sign up to set email alerts
|

Transferability of Cucumber Microsatellite Markers Used for Phylogenetic Analysis and Population Structure Study in Bottle Gourd (Lagenaria siceraria (Mol.) Standl.)

Abstract: Improved breeding for developing fruit quality in bottle gourd (Lagenaria siceraria (Mol.) Standl.) necessitates knowledge regarding its genetic diversity. To achieve this, a set of 108 locus-specific SSR markers has been developed in bottle gourd by cross-species transferability from 995 mapped Cucumis sativus SSR markers. During screening, 280 primer pairs amplified in the bottle gourd germplasm, which were further evaluated in a diverse set of 42 lines, resulting in 19 polymorphic, 89 monomorphic, 15 with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
2
12
3
Order By: Relevance
“…These values are comparatively higher than those reported by Sarao et al (2013) with 0.23 to 0.73 and Xu et al (2011) with 0.11 to 0.72 (mean = 0.4). Yildiz et al (2015) reported PIC values of 0.12 to 0.52 (mean = 0.15) in bottle gourd, whereas Bhawna et al (2015b) found PIC values of 0.05 to 0.54 (average = 0.33) using 19 SSR markers. The PIC defines a relative measure of the informativeness of a marker or discriminatory power of a polymorphic marker, which depends on the number of alleles and relative frequency of an allele in the population (Bhawna et al, 2015b;Gaikward et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These values are comparatively higher than those reported by Sarao et al (2013) with 0.23 to 0.73 and Xu et al (2011) with 0.11 to 0.72 (mean = 0.4). Yildiz et al (2015) reported PIC values of 0.12 to 0.52 (mean = 0.15) in bottle gourd, whereas Bhawna et al (2015b) found PIC values of 0.05 to 0.54 (average = 0.33) using 19 SSR markers. The PIC defines a relative measure of the informativeness of a marker or discriminatory power of a polymorphic marker, which depends on the number of alleles and relative frequency of an allele in the population (Bhawna et al, 2015b;Gaikward et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Yildiz et al (2015) reported PIC values of 0.12 to 0.52 (mean = 0.15) in bottle gourd, whereas Bhawna et al (2015b) found PIC values of 0.05 to 0.54 (average = 0.33) using 19 SSR markers. The PIC defines a relative measure of the informativeness of a marker or discriminatory power of a polymorphic marker, which depends on the number of alleles and relative frequency of an allele in the population (Bhawna et al, 2015b;Gaikward et al, 2008). In the present study, the highest PIC value was detected using marker LSR015 (0.84), closely followed by LSR020 (0.83).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…SSRs are used because of their codominant inheritance, multiallelic nature, abundance in the genome, and high reproducibility, but SSR marker development is time-consuming and costly. In this study, polymorphic SSRs were screened from the literature, indicating the transferability of SSRs from closely related species, which has also been found in other studies (Cui et al, 2008;Bhawna et al, 2015). Therefore, screening SSR markers from closely related species is a time-and money-saving method.…”
Section: Discussionmentioning
confidence: 55%
“…Numerous health benefits are reported in bottle gourd including its anti-cancerous (Saha et al, 2011), Cardio for detecting genetic diversity, genetic linkage mapping, association mapping and evolution analysis (Jiao et al, 2012). Despite bottle gourd being an important tropical vegetable crop, having abundant health benefits and proven for climate change adaptation strategies (Chimonyo and Modi, 2013), very limited molecular marker studies have been reported to study its genotyping, such as ISSR, SNP, SSR, RAPD (Bhawna et al, 2014;Xu et al, 2011;Bhawna et al, 2015;Sarao et al, 2014;Srivastava et al, 2014;Decker-Walters et al, 2001 respectively), but no study has been reported to characterize bottle gourd populations by constructing enriched SSR genomic library. To preserve the genetic richness of this crop, efforts must be directed towards the achievement of reliable collection and conservation strategies.…”
Section: Introductionmentioning
confidence: 99%